Kisi-kisi Soal dan Analisis dalam Evaluasi Pendidikan - Azhar, Dzul; Hasan, Ismail; K, Mahmud Darul; Amin, Ahmad Yasir Al; Ridho, Ahmad Rasyid (TSAQOFAH, 2025)
Evaluation activities in the world of education are an integral component in the learning program in addition to the learning plan (curriculum), learning objectives, forms of learning, learning methods (methods), and learning tools (media), and learning methods. This study aims to determine the function of the question grid. This study uses a qualitative approach, namely research conducted by observing the surrounding phenomena and analyzing them using scientific logic. This study also uses a descriptive method, namely research that attempts to describe the actual conditions in the field purely as they are in accordance with the context of the study. The conclusion of this paper is that the question grid must be made in the right way, but many teachers in making question grids are still far from perfect due to several factors including: Teachers still do not understand how to choose the right Basic Competencies. Many indicators contain material that should not be there. Evaluation in Education at least covers three things, namely; learning program design, program implementation, and the results achieved.